Islamic Theological Views on the Teachers' Position and Duties - Agus Salim Lubis (State Institute of Islamic Studies Imam Bonjol Padang, 2015)
Some people always underestimate  teachers. A  person as teachers do not preserve their personality; whereas, from the side of tauhid, teaching profession is a very noble job and should be given a high honor. Why? Because the tasks undertaken by the teachers have the relationship with the existence of what has been done by God, Allah, to all His creators, as teaching, educating, leading, guiding, and preserving. On the other hand, a teacher must have a personality with divine attributes (rabbaniyah), such as love and gentle, honest, virtuous, patient, has a broad and deep knowledge, clean or avoid sin, humble and forgiving, and others.   Keywords: Teacher, Theology, Islam. Copyright © 2015 by Al-Ta'lim All right reserved